Evaluating Soil Contamination Risks Using a Novel Combined Pollution Quality Index (CPQI) in Sulaymaniyah, Iraq - Midya Abdulqadr Abdulrahman; Zereen Jamal Ghafour; Nihad bahaaldin Salh (Sulaimani Journal for Engineering Sciences)
Soil is a great reservoir of nutrients and pollutants, and as such plays an important role in health and socio-ecological sustainability. Contaminants from agriculture, urbanization and industrial activities enter the soil which increases soil pollution and impose a big risk on human health. Soil samples from two different locations (Kostay Cham and Kani Goma) in Sulaymaniyah city were examined. The areas are two agricultural farms irrigated by water from stream and by wastewater respectively. Six different points were selected at two study areas at surface and at 60 cm depth for each point. While two water samples were collected at each site (pH, electric conductivity EC, DO, BOD5, TDS, TSS, salinity, turbidity, total alkalinity and hardness, with heavy metals Pb, Cd, Cu, Ni, Fe, and Zn) in Qilyasan stream water and wastewater determined. This study introduces a novel Combined Pollution Quality Index (CPQI) that integrates six weighted Indices-Nutrient Index, Salinity Index, Organic Matter Index, Sodium Adsorption Ratio (SAR) Index, Heavy Metal Risk Index, and Pollution Quality Index (PQI). Analytic Hierarchy Process (AHP) used to find weight values for each index. Chemical, physical and biological tests were carried for all soil samples such as; heavy metals, organic matter, nutrients, PH, TDS, EC. The results showed that the heavy metal concentration in all samples (surface and 60 cm depth) are within the allowable range. Generally higher levels of most heavy metals observed at 60 cm depth compared to surface samples. CPQI (combined pollution quality index) derived from all indices together to realize pollution index for each location, consequently all the CPQI values founded are below 1, meaning they fall under "Low Pollution" for all selected sites condition according to the limitations values, the highest value taken by the first location 60 cm deep result about 0.49 and lowest value 0.34 for the first location surface sample. this result is due to the high probability of absorption by plant roots and vegetables.